Core Spun Based Helical Auxetic Yarn: A Novel Structure for Wearable Protective Textiles. Issue 16 (28th November 2022) - Mushtaq, Bushra; Ahmad, Adnan; Ali, Zulfiqar; Qadir, Muhammad Bilal; Khaliq, Zubair; Irfan, Muhammad; Iqbal, M. Waqas; Jabbar, Abdul; Zulifqar, Adeel; Shahzad, Amir
ABSTRACT: Textile auxetic materials with negative Poisson's ratio (NPR) have potential applications in protective textile, filtration, and energy absorbance. However, cotton core-spun based auxetic textile is rarely investigated. In this study, cotton core-spun (Lycra)-based helical auxetic yarn (HAY) was developed, and the effects of core filament linear density on the auxetic behavior were studied. Core-spun cotton yarns of 8/1 Nec containing core filament (180, 260, and 420 D) were developed. Then, these core-spun yarns were wrapped with 50 D Dyneema filament at 393 twist/m to make the HAY. The diameter, NPR, and tensile strength of HAY were increased with increasing linear density of Lycra filament. Image analysis of HAY containing 420 D Lycra showed 57% diameter increase with the change in axial strain from 0 to 15 mm. The maximum auxetic behavior with NPR of −3.97 and tensile strength of 26.71 cN/tex was observed in 420 D Lycra-based HAY. This study proved that the cotton core spun-based HAY can be produced with significant auxetic properties for practically potential use in wearable protective textiles.